Synthesis gas production from water electrolysis, using the Electrocracking concept - Guerra, Luís (2018)
The present research work is focused on the production of synthesis gas by water electrolysis, using renewable electric energy and, further on, liquefied biomass as a carbon source necessary for obtaining carbon monoxide and carbon dioxide. In order to demonstrate and also optimize this process, this study comprised the influence of the electrolyte concentration, liquefied cork concentration, temperature and pressure and the main process outputs, such as: the flow rate of the produced gas, carbon monoxide, carbon dioxide and oxygen composition, as well as the energy consumed in the process. This gas can further on, be used for producing renewable synthetic fuels, such as: methane, methanol, dimethyl ether (DME), diesel, etc. The optimum operational conditions thus determined for this process, at laboratory scale, comprised the use of NaOH 1.2 M mixed with 20% (v/v) liquefied cork, as electrolyte. Applying these operating conditions a synthesis gas composed of 66.67% H2, 25.32% CO, 0.00% CO2 and 8.01% O2 was obtained at a flow rate of 8.31 L/h, consuming a power of 7.75 Wh/L. Also, the analysis of the residual biomass deposited in the electrodes showed some changes in the initial structure, as expected.